Dual-modified cationic liposomes loaded with paclitaxel and survivin siRNA for targeted imaging and therapy of cancer stem cells in brain glioma - Xiyang Sun; Ying Chen; Hui Zhao; Guanglei Qiao; Meiyang Liu; Chunlei Zhang; Daxiang Cui; Lijun Ma (Taylor & Francis Group, 2018)
Development of safe, efficient nanocomplex for targeted imaging and therapy of cancer stem cells in brain glioma has become a great challenge. Herein, a low-density lipoprotein receptor-related protein and a RNA aptamer bound CD133 were used as dual-targeting ligands to prepare dual-modified cationic liposomes (DP-CLPs) loaded with survivin siRNA and paclitaxel (DP-CLPs-PTX-siRNA) for actively targeting imaging and treating CD133+ glioma stem cells after passing through the blood-brain barrier. After being administrated with DP-CLPs-PTX-siRNA nanocomplex, DP-CLPs showed a persistent target ability to bind glioma cells and brain microvascular endothelial cells (BCECs) and to deliver drugs (PTX/siRNA) to CD133+ glioma stem cells. Prepared DP-CLPs-PTX-siRNA nanocomplex showed very low cytotoxicity to BCECs, but induced selectively apoptosis of CD133+ glioma stem cells, and improved CD133+ glioma stem cells' differentiation into non-stem-cell lineages, also markedly inhibited tumorigenesis, induced CD133+ glioma cell apoptosis in intracranial glioma tumor-bearing nude mice and improved survival rates. In conclusion, prepared DP-CLPs-PTX-siRNA nanocomplex selectively induced CD133+ glioma stem cell apoptosis in vitro and in vivo exhibits great potential for targeted imaging and therapy of brain glioma stem cells.